2016
DOI: 10.1128/aac.01334-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High N -Acetylcysteine Concentrations on Antibiotic Activity against a Large Collection of Respiratory Pathogens

Abstract: The effect of high N-acetylcysteine (NAC) concentrations (10 and 50 mM) on antibiotic activity against 40 strains of respiratory pathogens was investigated. NAC compromised the activity of carbapenems (of mostly imipenem and, to lesser extents, meropenem and ertapenem) in a dose-dependent fashion. We demonstrated chemical instability of carbapenems in the presence of NAC. With other antibiotics, 10 mM NAC had no major effects, while 50 mM NAC sporadically decreased (ceftriaxone and aminoglycosides) or increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
4
19
0
3
Order By: Relevance
“…On the contrary, NAC alone inhibited bacterial growth without inducing the SOS response (Tukey multiple comparisons after significant ANOVA, P=0.0003). This result is in line with previous studies that reported NAC antibacterial properties against a range of bacterial pathogens (37,40,41).…”
Section: Nac Reduces Cip-mediated Induction Of the Sos Responsesupporting
confidence: 93%
See 3 more Smart Citations
“…On the contrary, NAC alone inhibited bacterial growth without inducing the SOS response (Tukey multiple comparisons after significant ANOVA, P=0.0003). This result is in line with previous studies that reported NAC antibacterial properties against a range of bacterial pathogens (37,40,41).…”
Section: Nac Reduces Cip-mediated Induction Of the Sos Responsesupporting
confidence: 93%
“…On the contrary, NAC alone inhibited bacterial growth without inducing the SOS response (Tukey multiple comparisons after significant ANOVA, P=0.0003). This result is in line with previous studies that reported NAC antibacterial properties against a range of bacterial pathogens (Jang, Bak, and Cha 2017;Landini et al 2016;Zhao and Liu 2010). Additionally, we verified that the differences in the final optical density observed upon different treatments do not directly bias SOS induction measured as GFP fluorescence (Supplementary figure S3).…”
Section: Nac Reduces Cip-mediated Induction Of the Sos Responsesupporting
confidence: 92%
See 2 more Smart Citations
“…It is usually used as a mucolytic agent and an antioxidant to react with mucous bronchial secretions and free radicals. NAC can affect the stability and compromise the activity of carbapenems [32]. It also decreases the activity of coagulation factors in plasma, and intravenous NAC may interfere with the sulfhydryl groups on these factors [25, 33].…”
Section: Discussionmentioning
confidence: 99%